2022
DOI: 10.3390/genes13060979
|View full text |Cite
|
Sign up to set email alerts
|

ATP-dependent DNA helicase (TaDHL), a Novel Reduced-Height (Rht) Gene in Wheat

Abstract: In wheat, a series of dwarf and semi-dwarf plant varieties have been developed and utilized worldwide since the 1960s and caused the ‘Green Revolution’. To date, 25 reduced-height (Rht) genes have been identified, but only several genes for plant height (PH) have been isolated previously. In this study, we identified a candidate gene, ATP-dependent DNA helicase (TaDHL-7B), for PH via QTL mapping and genome-wide association study (GWAS) methods. We knocked out this gene using the CRISPR/Cas9 system in variety ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In addition, many genes could be cloned for other traits using RIL populations. For example, we have cloned a quality gene XIP (Xylanase Inhibitor Protein) (Sun et al, 2022) and a Rht gene TaDHL ( ATP-dependent DNA helicase ) (Guo et al, 2022) from QTLs of the TL-RILs. Seven other Rht genes were also confirmed via CRISPR/Cas9 technology from QTLs of the TL-RILs and “Shannong0431 × Lumai21” RILs (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many genes could be cloned for other traits using RIL populations. For example, we have cloned a quality gene XIP (Xylanase Inhibitor Protein) (Sun et al, 2022) and a Rht gene TaDHL ( ATP-dependent DNA helicase ) (Guo et al, 2022) from QTLs of the TL-RILs. Seven other Rht genes were also confirmed via CRISPR/Cas9 technology from QTLs of the TL-RILs and “Shannong0431 × Lumai21” RILs (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are some methods about gene mining. For example, whole genome association analyses to locate gene loci related to plant height ( Guo et al., 2022 ), yield ( Li et al., 2021 ), and disease resistance ( Tsai et al., 2020 ). They only localize the relevant gene loci into a segment containing many candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Using the QTL location of UG-Map for TL-RILs, we previously cloned two genes, the XIP ( Xylanase Inhibitor Protein ) gene, which regulates the SDS-sedimentation value and dough stability time [ 40 ], and the TaDHL ( ATP-dependent DNA helicase ) gene, which regulates the plant height [ 41 ]. These results further showed that the candidate genes in this study are favorable for corresponding gene cloning.…”
Section: Discussionmentioning
confidence: 99%